Mechanics of Cutting and Boring. Part 1: Kinematics of Transverse Rotation Machines. - Mellor,Malcolm (1975)
This report, which is one of a series on the mechanics of cutting and boring in rock, deals with the kinematics of machines such as disc saws, drum millers, rotary planers and bucket-wheel excavators, in which the rotary cutting element revolves about an axis that is normal to the direction of working travel. The analysis covers the geometry and motion of various components of the cutting system, touching on topics such as chipping depth, cutting transfer, excavation rate, tool trajectories, tool speeds, rake and relief angles on tools and tool layout. Worked examples are given to illustrate various points.